2018
DOI: 10.1097/ta.0000000000002017
|View full text |Cite
|
Sign up to set email alerts
|

Association of pain after trauma with long-term functional and mental health outcomes

Abstract: Therapeutic/Care management, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…Injured patients who experience chronic pain are more likely to screen positive for posttraumatic stress disorder and to experience functional limitations while being less likely to be back at work or school one year post-injury. 10,19 The sheer prevalence of chronic pain in both groups in the current study, which is consistent with prior reports in the general trauma population, 20e22 is rather remarkable with 36% of the overall cohort reporting chronic pain requiring medication 6e12 months postinjury. Even with changes in opioid prescribing habits over the last decade, the prevalence of chronic pain and pain requiring medication remains extremely high.…”
Section: Discussionsupporting
confidence: 91%
“…Injured patients who experience chronic pain are more likely to screen positive for posttraumatic stress disorder and to experience functional limitations while being less likely to be back at work or school one year post-injury. 10,19 The sheer prevalence of chronic pain in both groups in the current study, which is consistent with prior reports in the general trauma population, 20e22 is rather remarkable with 36% of the overall cohort reporting chronic pain requiring medication 6e12 months postinjury. Even with changes in opioid prescribing habits over the last decade, the prevalence of chronic pain and pain requiring medication remains extremely high.…”
Section: Discussionsupporting
confidence: 91%
“…These important pre-injury characteristics should be included in future studies to further investigate important risk factors for mental health problems after physical injury. Additionally, other outcome variables not included in this study, such as pain levels, are also found to be associated with mental health and functional outcome in other studies (Herrera-Escobar, Kaafarani, Velmahos, Salim, & Haider, 2018 ).…”
Section: Methodsmentioning
confidence: 66%
“…Failure to provide adequate relief from pain can result in prolonged recovery, post-traumatic stress, and delayed return to functionality. [18][19][20][21][22] At the same time, exposure to opioids has been associated with future opioid misuse. 4,23 This poses a great challenge for providers in managing both short-and long-term welfare of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Many of these children experience moderate to severe pain after trauma, and opioids are one way that pain is treated. [11][12][13][14][15][16][17] Inadequately managed pain can lead to significant long-term consequences, such as post-traumatic stress and substance abuse 7,[18][19][20][21][22] ; however, early exposure to opioids has also been linked to similar outcomes. 4,23,24 Opioids are often first-line treatment for moderate and acute pain after trauma, yet many trauma centers lack clear guidelines for when opioids are indicated in the pediatric trauma population and for the maximum cumulative amount of opioid to administer to pediatric patients.…”
mentioning
confidence: 99%